Variation in Environmental Conditions and Biodiversity Between Contrasting Intertidal Habitats Across Multiple Spatial Scales on European Rocky Shores - Luca Rindi; Ludovica Pedicini; Iacopo Bertocci; Lisandro Benedetti‐Cecchi; Dan Smale; Fernando Tuya; Adriana Rodriguez; Mariachiara Chiantore; Valentina Asnaghi; Paolo Albicini; Rolf Karez; Dominique Davoult; et al. (Global Ecology and Biogeography, 2026)
Aim Foundation species sustain biodiversity by providing habitat, resources, and protection from environmental stress. However, their influence on environmental severity and variability and their role in shaping diversity across spatial scales remain poorly understood. We conducted a large‐scale study to assess how environmental conditions and community diversity vary between areas with and without canopy‐forming macroalgae across local to regional spatial scales. Location Latitudinal range from 28°34′N to 54°11′N, encompassing both the Northeast Atlantic and Western Mediterranean regions. Time Period 2019–2020. Major Taxa Studied Marine macroalgae and benthic invertebrates. Methods Using a standardised nested sampling design across 13 sites in two marine regions (the Northeast Atlantic and Western Mediterranean) we compared the intensity and variability of temperature and light intensity, as well as community α‐ and β‐diversity, between intertidal rocky areas with and without canopy‐forming macroalgae. Data were analysed by means of linear mixed‐effects models. Results There were regional differences in variations of environmental conditions between habitats: NE Atlantic macroalgal canopies were characterised by lower environmental extremes and variability—especially in summer—than open rock areas, whereas differences between habitats were small in the W Mediterranean. Likewise, differences in α‐ and β‐diversity between habitats were region‐specific and scale‐dependent: in the NE Atlantic, α‐diversity was higher in the presence of canopies than in open rock areas from local to regional scales, while β‐diversity decreased in canopy stands with increasing spatial scale. In the W Mediterranean, α‐diversity was higher under canopies than on open rock at the regional scale, whereas β‐diversity was higher under canopies at small to intermediate scales. Main Conclusions Our results support the view that key environmental conditions and biodiversity on intertidal rocky shores differ between areas characterised by the presence or absence of canopy‐forming macroalgae acting as foundation species, across a hierarchy of spatial scales.